Transfer Pricing, Income Smoothing, Audit Committee, and Tax Avoidance: Examining the Moderating Effect of Fincancial Constraint - Saota, Adrianus; Siburian, Matondang Elsa; Simorangkir, Enda Noviyanti (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2026)
This study examines the influence of transfer pricing aggressiveness, income smoothing, and audit committee on tax avoidance, with financial constraints serving as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2018–2023. Using a quantitative approach, the research utilizes secondary data derived from companies’ annual financial statements. A total of 61 companies were selected through purposive sampling, resulting in 366 firm-year observations. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4 to evaluate both direct and moderating relationships among variables. The empirical results show that transfer pricing aggressiveness has a positive yet insignificant effect on tax avoidance, suggesting that regulatory enforcement, such as mandatory transfer pricing documentation, may reduce the opportunity to exploit related-party transactions for tax benefits. Income smoothing and audit committee also show negative and insignificant effects, indicating that neither practice plays a dominant role in influencing tax avoidance behavior. In contrast, financial constraints exhibit a negative and significant effect on tax avoidance, implying that financially constrained firms tend to adopt more conservative tax strategies due to limited resources and higher risk considerations. However, financial constraints fail to moderate the relationships between each independent variable and tax avoidance. These findings provide insights for regulators, policymakers, and practitioners on understanding the determinants of tax avoidance and highlight the importance of financial conditions in shaping corporate tax behavior